Globalization and change : perspectives from Punjab : essays in honour of Prof. S.S. Gill - Gill, Sucha Singh; Ghuman, Ranjit Singh; Surjit Singh; Brar, Jaswinder Singh (Jaipur : Rawat Publications, 2010)
Contributed articles with special reference to the state of Punjab, India.
Includes bibliographical references.
"Professor Sucha Singh Gill's publications": p. xiii-xviii.
Keywords: GLOBALIZATION -- ECONOMIC ASPECTS -- INDIA -- PUNJAB; NATION-STATE AND GLOBALIZATIONA -- INDIA -- PUNJAB; PUNJAB (INDIA) -- ECONOMIC CONDITIONS; INDIA -- ECONOMIC POLICY